Health Students’ Satisfaction Level with Clinical Practice Experience at Prabumulih City General Hospital - Dedianto Dedianto (International Journal of Health and Medicine, 2025)
This study explores the satisfaction levels of health science students with their clinical practice experiences at Prabumulih City General Hospital. Clinical practice serves as a vital component of health education, enabling students to apply theoretical knowledge in real healthcare settings. Using a qualitative phenomenological approach, the research sought to gain an in-depth understanding of students’ subjective experiences. Data were collected through in-depth interviews, focus group discussions, and participatory observations with students undergoing clinical practice. Thematic analysis and data triangulation ensured the validity of findings. Results revealed that students’ satisfaction was influenced by hospital facility quality, guidance from medical staff and lecturers, and interactions with patients and their families. Moreover, challenges in managing clinical cases and the social support received also shaped students’ satisfaction. The study recommends improving clinical practice facilities, strengthening supervision and mentoring by medical personnel, and providing greater institutional support. It also suggests that health education institutions design clinical practice programs more closely aligned with student needs and professional expectations.